ANALISIS PENGARUH PENGALIHAN PAJAK BUMI DAN BANGUNAN PEDESAAN DAN PERKOTAAN (PBB P2) TERHADAP PENERIMAAN PENDAPATAN DAERAH KOTA KEDIRI TAHUN 2012 DAN 2013 - LESTARI, VONI (Jurnal Akuntansi AKUNESA, 2014)
Tax Law and Regional Retribution Act No. 28 of 2009 regulated about handed tax property of rural an urban sectors. Before it, land and building tax revenue be a central government revenue, but now land and building tax be regional revenue. This law is one of the goal of self government. So, all about land and building tax from collection of data, administration until land and building tax service was held by regional government. Purpose of this research is to know delivery influence of land and building tax rural and urban sectors to local revenue, it will increase or decrease. Method of this research is qualitative discriptive by interviewed informant. The result of this research is by delivery land and building tax rural and urban sectors increase local revenue of Kediri City.Keywords: Tax Law, local revenue, land and building tax.